Strategi Pengelolaan Arsip Pembinaan Kearsipan Menjadi Informasi - Herawan, Lufi (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
The development of information and communication technology is developing very quickly so that it can help us, including in managing records. At the stages of use and maintenance activities, there are activities processing records and present records as information, so it is necessary to know the strategy for processing records into information utilizing technological developments for facilitating decision making. This research is descriptive research with case study and desk research types. Through this research, the strategies of processing records into information were obtained using text converters to digital text, automatic records readers, and automatic records summarizers. The strategy starts from creating digital records, converting writing into digital text, storing, reading and summarizing automatic records, storing data in databases, and presenting information.